Characterizing the influencing factors in a novel repairing material for concrete structures by AC impedance spectroscopy. (15th April 2022) - Ma, Cong; Liu, Yuantao; Song, Danqing; Cao, Lei; He, Fuqiang; Liu, Xiaoli; Zhou, Haijun
Abstract: This research systematically characterizes the working mechanism of the influencing factors, e.g., magnesia to phosphate (M/P) ratio, borax, sodium tripolyphosphate (STP), fly ash (FA), and silica fume (SF), in magnesium phosphate cement (MPC) from the initial 1 h hydration age by a non-destructive testing method- AC impedance spectroscopy (ACIS). The results show that the M/P ratio significantly affects MPC, and its influencing mechanism is changed during the whole hydration period. At the initial period (within 6 h), a higher M/P ratio causes a quicker hydration rate. During the later stage, a higher M/P ratio relates to a lower strength growth potential. The resistance values collaborate with the compressive strength well. The commonly used borax and STP have different influences in MPC. Borax retards the acid-based reaction, while STP has little retarding effect. STP improves the hydration process and microstructure formation from the initial age. Both the mineral admixtures: FA and SF, reduce the early age properties of MPC. As the hydration continues, they continuously decrease the porosity and optimize the pore size distribution. SF has a smaller particle size and a more significant improvement effect than FA. As ACIS detects, MPC has higher early strength, faster strength increasing rate, and finer pore size distribution than other cement-based materials, e.g., AAM and UHPC. The results are helpful to improve the performances of this novel repairing material for hydraulic concrete structures. Highlights: MPC has a finer pore size distribution than AAM and UHPC. The M/P ratio has a different influencing mechanism at the initial period and the later stage. Borax has a good retarding effect, while STP improves the hydration process and microstructure formation. FA and SF, having a smaller particle size than magnesia, can decrease the porosity and optimize the pore size distribution.